1998
DOI: 10.1073/pnas.95.17.10106
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-transforming protein latent infection membrane protein 1 activates transcription factor NF-κB through a pathway that includes the NF-κB-inducing kinase and the IκB kinases IKKα and IKKβ

Abstract: The Epstein-Barr virus oncoprotein latent infection membrane protein 1 (LMP1) is a constitutively aggregated pseudo-tumor necrosis factor receptor (TNFR) that activates transcription factor NF-B through two sites in its C-terminal cytoplasmic domain. One site is similar to activated TNFRII in associating with TNFR-associated factors TRAF1 and TRAF2, and the second site is similar to TNFRI in associating with the TNFRI death domain interacting protein TRADD. TNFRI has been recently shown to activate NF-B throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
121
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 40 publications
(70 reference statements)
7
121
1
2
Order By: Relevance
“…Consequently, NF-kB is released and translocates to the nucleus where it binds to its cognate sequences within the promoter/regulatory regions of many genes. The TES1/CTAR1 and TES2/CTAR2 domains of LMP1 activate NF-kB along the same pathway since overexpression of dominant-negative mutants of TRAF2, NIK, IKKa and IKKb can each inhibit LMP1-induced activation of NF-kB Kaye et al, 1996;Sylla et al, 1998).…”
Section: Lmp1 Activates Rel/nf-kb Through Tnf-r Associated Signalingmentioning
confidence: 99%
“…Consequently, NF-kB is released and translocates to the nucleus where it binds to its cognate sequences within the promoter/regulatory regions of many genes. The TES1/CTAR1 and TES2/CTAR2 domains of LMP1 activate NF-kB along the same pathway since overexpression of dominant-negative mutants of TRAF2, NIK, IKKa and IKKb can each inhibit LMP1-induced activation of NF-kB Kaye et al, 1996;Sylla et al, 1998).…”
Section: Lmp1 Activates Rel/nf-kb Through Tnf-r Associated Signalingmentioning
confidence: 99%
“…In lymphoid cells, where rearrangement and somatic mutations in the antigen receptor are the most lineage-specific events, analysis of the immunoglobulin heavy chain locus in HLRSCs clearly implicated germinal center B cells as the HLRSC origin (Braeuninger et al, 1997;Ohno et al, 1997). The neoplastic Reed-Sternberg cells in Hodgkin's lymphoma (HL) are characterized by constitutively activated NF-κB (Bours et al, 1992), due to over-expression of potent NF-κB-activating TNF receptor family proteins (CD40, CD30, or EBV LMP1) (Cabannes et al, 1999;Sylla et al, 1998) or mutation in the inhibitor of the NF-κBα gene (IκBα) Krappmann et al, 1999). However, the pathogenesis of HL remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of the tumor necrosis factor-receptor family proteins (CD30, CD40 and LMP1) has the potential to activate NF-κB (Cabannes et al, 1999;Sylla et al, 1998). Given that HLRSCs are derived from B lymphocytes and that LMP1 is expressed exclusively in EBV-positive HLRSCs, as well as that CD99 repression by LMP1 is associated with Reed-Sternberg cell morphology, it is important to determine how LMP1 is involved in the pathogenesis of HL (Boiocchi et al, 1992;Herbst et al, 1990;1992a;1992b).…”
Section: Introductionmentioning
confidence: 99%
“…This EBV-derived protein has previously been shown to be important in transformation and can activate NF-kB. 16,17,[28][29][30] Furthermore, the lymphotoxin gene promoter is regulated, at least in part, by the NF-kB transcription factor. 31,32 The logical extension of these observations was to determine if LMP1 expression is responsible for autocrine lymphotoxin production in EBV-positive B cells.…”
Section: Nf-kb Inhibition Decreases Lymphotoxin Productionmentioning
confidence: 99%
“…[24][25][26][27] With regard to NF-kB, it has been shown that LMP1 mimics the phosphorylating action of the IkB kinase and, hence, increases NF-kB activation by up to 30-fold. [28][29][30] Of interest, the lymphotoxin gene contains a high-affinity kB element, which, when bound to the NF-kB transcription factor, contributes to the production of lymphotoxin. 31,32 However, a direct relationship between LMP1, NF-kB activation, and lymphotoxin production in EBV-infected lines has not been explored.…”
Section: Introductionmentioning
confidence: 99%